2019 18th Brazilian Symposium on Computer Games and Digital Entertainment (SBGames) 2019
DOI: 10.1109/sbgames.2019.00025
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Emotion Style in Human Faces and Avatars

Abstract: This paper describes a computational study regarding the way real humans manifest their facial expressions and emotions and how other people perceive that when applied to virtual humans. We propose a new metric for measuring individuals' emotion style where subjects were recorded while expressing the six basic emotions (happiness, fear, disgust, anger, surprise and sadness). With this metric, we were able to group the subjects into four different clusters and provide evidence that shows a visual correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Besides the modeling of different emotions, we would like to make this experience more personal, as it would be with a friend. In this topic, Melgare et al [Melgare et al 2019] suggested the existence of emotion styles, where each person would have their own way to demonstrate an emotion. In this sense, one interesting future work would be to endow Arthur/Bella with the ability to identify such style on the face of the user and mimic it.…”
Section: Final Remarksmentioning
confidence: 99%
“…Besides the modeling of different emotions, we would like to make this experience more personal, as it would be with a friend. In this topic, Melgare et al [Melgare et al 2019] suggested the existence of emotion styles, where each person would have their own way to demonstrate an emotion. In this sense, one interesting future work would be to endow Arthur/Bella with the ability to identify such style on the face of the user and mimic it.…”
Section: Final Remarksmentioning
confidence: 99%
“…Besides the modeling of different emotions, we would like to make this experience more personal, as it would be with a friend. In this topic, Melgare et al [23] suggested the existence of emotion styles, where each person would have their own way to demonstrate an emotion. In this sense, one interesting future work would be to endow Arthur/Bella with the ability to identify such style on the face of the user and mimic it.…”
Section: Final Remarksmentioning
confidence: 99%